Determinant Tax Compliance by Tax Fiscus Perception - Purwati Harjayani; Indriyana Puspitosari (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
Tax has an important role in the country, namely as one of the largest sources of revenue. The existence of obstacles in tax revenue makes the government or in this case the Directorate General of Tax implement several new policies aimed at increasing tax compliance. However, the target of tax revenue is still not realized in accordance with the planning that has been done.Thus the study aims to determine the effect of the Automatic Exchange of Information system, the modern tax administration system, and the tax audits of tax compliance. The object examined in this study is Tax Office in the area of Soloraya. This type of research is quantitative research. The population in this study is a tax employee who is in the position of account representative (AR) and functional examiner in the Tax Office in the Soloraya. The sample of this study was selected using a simple random sampling technique and obtained 75 respondents. This study uses primary data obtained from questionnaires that have been filled by respondents. The results of the study indicate that the Automatic Exchange of Information System and tax audit have an effect on tax compliance, while the modern tax administration system has no effect on tax compliance .